STRATEGI GURU DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS ANAK USIA 4-5 TAHUN MELALUI MEDIA KARTU ANGKA DI KOBER TUNAS BANGSA KOTA SERANG - Suedah; Nuryati; Umalihayati (STKIP Subang, 2026)
Motivated by the lack of teachers in strategies in learning, this study aims to find out how successful teachers' strategies are in developing the ability of early childhood aged 4-5 years in critical thinking through the media of number cards at the Kober Tunas Bangsa institution, Curug district, Serang City. In this study, descriptive qualitative research was carried out with data collection techniques in qualitative research carried out directly in the field using observation, interviews, and documentation activities. The results of the research were obtained that the way to develop critical thinking in early childhood in Kober Tunas Bangsa, Serang City was quite good using number card media and the teachers were very helpful in creating a fun learning atmosphere. It can be concluded that, number cards are one of the most effective media to improve early childhood abilities in terms of critical thinking.